A Forgotten Case of Madura Foot - Dwiana Savitri (Green Publisher, 2025)
Mycetoma is a chronic, suppurative, and debilitating granulomatous infection primarily found in tropical and subtropical regions. The World Health Organization has classified it as a neglected tropical disease. The clinical diagnosis is typically based on a classic triad of localized swelling, the formation of sinus tracts, and the production of grains or granules. However, atypical presentations of the disease are also observed. Mycetoma is divided into two categories: eumycetoma, which is caused by fungal organisms, and actinomycetoma, which is caused by bacterial agents. While the clinical features of both types are similar, a precise diagnosis is crucial, as treatment approaches differ between the two. The treatment of mycetoma involves surgical debulking to remove the bulk of the lesion, followed by an extended course of medical therapy. This combined approach has become the standard due to the long duration of the disease and the often suboptimal response to treatment. The prolonged course of mycetoma necessitates careful management, as the disease can be difficult to treat effectively with just one modality. Therefore, early detection and accurate diagnosis are key to determining the most appropriate treatment plan for each patient.